Subjective measurements (rating theory) - Romanchak, Vasily M. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
In this paper, a version of the theory of measurements is proposed. The introduction provides links to papers that discuss various measurement theories. In order for a measurement to satisfy strict mathematical criteria, it is necessary to confirm the quantitative nature of the attributes. However, most dimensions in psychology do not satisfy these strict criteria. The paper assumes that this state of affairs is explained not by the lack of competence among specialists, but by the lack of a measurement theory within which such a test could be performed. It is concluded that, within the framework of the existing theory of representative measurements, such a check is not provided. In this connection, the paper proposes to use the theory of ratings instead of a representative theory of measurements. A brief formulation of rating theory is given. It is emphasized that using the theory of ratings it is possible to empirically confirm the quantitative nature of the measured attribute. A real-world example of effective data analysis is analyzed. The application of rating theory allows us to eliminate the paradoxical contradiction between the laws of Fechner and Stevens and confirm the quantitative nature of the values obtained by subjective measurement methods.
Keywords: expert estimates; rating; Fechner law; Stevens law; measurement theory